2022
DOI: 10.3389/fneur.2022.914048
|View full text |Cite
|
Sign up to set email alerts
|

Association Between A-Waves and Outcome in Pediatric Guillain-Barré Syndrome

Abstract: IntroductionTo examine the importance of abundant A-waves in electrophysiological classification and prognosis of pediatric Guillain-Barré Syndrome (GBS).MethodsA single-center and retrospective study enrolling 65 children-patients, aged 16 years and younger, with clinically diagnosed GBS between 2013 to 2020. Hughes grade was used to assess functional disability at nadir, 1 month, and 6 months after symptom onset. Patients were divided into 2 groups according to the presence of abundant A-waves. Clinical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, many studies have shown that the metabolic by-products from having diabetes, particularly when it is poorly controlled, damage the small unmyelinated peripheral nerve function prior to the large myelinated nerve fibre [5]. Sympathetic skin response (SSR), as an objective electrophysiological marker to evaluate the autonomic unmyelinated nerve fibre function, has been used in the diagnosis and prognosis assessment of many diseases, such as pediatric Guillain-Barré syndrome [6], amyotrophic lateral sclerosis [7], multiple sclerosis [8], and adult diabetes mellitus [9], etc. The SSR study of pediatric diabetes mellitus is rare, therefore, the purpose of our study is to explore SSR characteristics in children living with T1DM and analyze the value of early diagnosis and follow-up in T1DM complicated with DPN.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have shown that the metabolic by-products from having diabetes, particularly when it is poorly controlled, damage the small unmyelinated peripheral nerve function prior to the large myelinated nerve fibre [5]. Sympathetic skin response (SSR), as an objective electrophysiological marker to evaluate the autonomic unmyelinated nerve fibre function, has been used in the diagnosis and prognosis assessment of many diseases, such as pediatric Guillain-Barré syndrome [6], amyotrophic lateral sclerosis [7], multiple sclerosis [8], and adult diabetes mellitus [9], etc. The SSR study of pediatric diabetes mellitus is rare, therefore, the purpose of our study is to explore SSR characteristics in children living with T1DM and analyze the value of early diagnosis and follow-up in T1DM complicated with DPN.…”
Section: Introductionmentioning
confidence: 99%